Changes of Central Corneal Thickness After Phacoemulsification (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Preservation of corneal endothelial integrity is crucial for optimal visual recovery following phacoemulsification cataract surgery. Central Corneal Thickness (CCT) serves as an indirect indicator of postoperative endothelial function. The purpose of the study is to evaluate the changes in central corneal thickness before and after uneventful phacoemulsification among patients with age-related cataract. Materials and methods: This prospective observational study included 49 patients underwent phacoemulsification at Chittagong Medical College Hospital from January 2021 to December 2021. CCT was measured preoperatively and on postoperative day 1, day 7 and day 30 using an ultrasound pachymeter. Visual status and postoperative complications were assessed. Data were analyzed using paired t-tests, with p < 0.05 considered statistically significant. Results: The mean age of the patients was 57.37±10.62 years (Range: 51-75), with a slight male predominance (53.1%). Grade II cataracts were the most common (51.0%). The mean preoperative CCT was 538.12 ± 8.45 μm. Postoperative CCT increased significantly on day 1 (614.84 ± 12.56 μm) and day 7 (582.31 ± 14.20 μm) (p < 0.001). By day 30, CCT returned near baseline (539.94 ± 8.19 μm) with no significant difference from preoperative values (p = 0.283). Corneal edema occurred in 6 patients (12.2%); no cases of infection or posterior capsular rupture were recorded. Conclusion: Phacoemulsification causes a transient increase in CCT during the early postoperative period, which typically resolves by 30 days, indicating preserved endothelial recovery.Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 101-105